2019
DOI: 10.1111/cei.13307
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm as an IgG4-related disease

Abstract: Summary The objectives of this study were to evaluate patients with aortic abdominal aneurysm (AAA) with regard to immunoglobulin (Ig)G4‐related disease (IgG4‐RD). IgG4‐RD represents a recently defined condition comprised of a collection of disorders characterized by IgG4 hypergammaglobulinemia, the presence of IgG4‐positive plasma cells in organs affected with fibrotic or sclerotizing changes and typical histopathological features. It was identified as a possible cause of vasculitis in large vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Despite this high IgG4 burden in studies from Japan, Koo et al reported 3 out of 29 positive aortic cases (10.9%) from Korea [ 29 ]. The largest study to date stems from the Czech Republic and reported 7 out of 114 AAA patient samples (6.1%) that were positive for IgG4-related disease, comparable to the results shown here ( Table 1 , Figure 1 , Supplementary Figure S1 ) [ 13 ]. Hence, one could hypothesize a different disease distribution over different ethnicities; this may, however, harbor selection and reporting bias, also including aneurysm sizes and emergency procedures, when, i.e., no sample can be acquired during surgery.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite this high IgG4 burden in studies from Japan, Koo et al reported 3 out of 29 positive aortic cases (10.9%) from Korea [ 29 ]. The largest study to date stems from the Czech Republic and reported 7 out of 114 AAA patient samples (6.1%) that were positive for IgG4-related disease, comparable to the results shown here ( Table 1 , Figure 1 , Supplementary Figure S1 ) [ 13 ]. Hence, one could hypothesize a different disease distribution over different ethnicities; this may, however, harbor selection and reporting bias, also including aneurysm sizes and emergency procedures, when, i.e., no sample can be acquired during surgery.…”
Section: Discussionsupporting
confidence: 82%
“…Here, the involvement of the recognized systemic inflammatory disorder known as immunoglobulin G4 (IgG4)-related disease has been linked to AAA by many groups, suggesting approx. 5–10% of all AAAs; however, up to 57% of inflAAA cohorts appear to be IgG4 positive to varying degrees [ 12 , 13 , 14 , 15 , 16 ]. Hence, diagnostic criteria involving both histology and blood sampling have been established to define inflammatory and IgG4-positive AAA.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-γ and IL-17 secreted by CD8+ T-cells and Th17 CD4+ T-cells have also been implicated in AAA pathogenesis [ 394 , 395 , 396 ]. B-cell-derived immunoglobulins such as IgG4 and IgE drive macrophage and mast cell activation and degranulation [ 397 , 398 ]. Regulatory CD4+ T-cells have a protective function by releasing anti-inflammatory cytokines such as IL-10 and TGF-β [ 399 , 400 , 401 ], but both regulatory CD4+ cells and their mediators are reduced in AAA patients [ 402 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Les nodules cardiaques sont très rares dans la maladie associée aux Ig G4 [21]. Des atteintes anévrysmales des artères coronaires, de l'aorte et des cas d' aortite ont été décrites [22][23][24][25].En fonction de la localisation des nodules, on peut noter un retentissement sur la fonction cardiaque [21].…”
Section: Discussionunclassified